Surreptitious Communication Design. - Hirsch, Tad (Design Issues)
The article examines surreptitious communication design (SCD), a framework for designing communication systems and campaigns that address political contexts. Particular focus is given to opposition to social change from those how have a vested interesting in maintaining the status quo. Additional topics discussed include "design for good" (D4G) movement, which aims to promote social change through design, strategies for SCD and how two of the common tactics of SCD are coding and cloaking. The design of two anti-human trafficking campaigns is also explored as is the National Human Trafficking Resource Center (NHTRC).